Diosbulbin B-induced liver injury in mice and its mechanism. (July 2014) - Ma, Yibo; Niu, Chengwei; Wang, Junming; Ji, Lili; Wang, Zhengtao
Dioscorea bulbifera L., a commonly used medicinal plant in China, is reported to induce hepatotoxicity. The present study is undertaken to investigate the hepatotoxicity induced by diosbulbin B (DB), a diterpene lactone isolated from D. bulbifera L., and to further explore its underlying mechanism. DB was administered to mice at the doses of 0, 16, 32, and 64 mg/kg once daily for 12 consecutive days. Liver injury induced by DB was evidenced by the increased activity of serum alanine aminotransferase (ALT), aspartate aminotransferase (AST), and alkaline phosphatase (ALP). Liver histological evaluation showed that the mice treated with DB exhibited liver damage with the swelling of hepatocytes. Further results showed that the amount of malondialdehyde (MDA) in the liver was increased in mice treated with DB, while the glutathione amount and the enzymatic activity of glutathione peroxidase (GPx), glutathione-S-transferase (GST), copper/zinc–superoxide dismutase (CuZn-SOD), manganese-SOD (Mn-SOD), and catalase (CAT) were all decreased. DB also decreased the gene expression of CuZn-SOD and CAT. Taken together, our results indicate that oral administration of DB for 12 consecutive days can lead to the oxidative stress liver injury in mice.